Role of MicroRNAs in Protective Effects of Forsythoside A Against Lipopolysaccharide-Induced Inflammation in Bovine Endometrial Stromal Cells - Lv, Haimiao; Yan, Chenbo; Deng, Lixin; Peng, Zhan; Yang, Dexin; Hu, Wenjv; Ding, Xuefen; Tong, Chao; Wang, Xinzhuang (Frontiers in Veterinary Science, 2021)
Bovine endometrial stromal cells (bESCs) are exposed to a complex environment of bacteria and viruses due to the rupture of epithelial cells after delivery. Inflammatory responses are elicited by the activation of host pattern recognition receptors through pathogen-related molecules such as lipopolysaccharides (LPS) on the cell membrane. Forsythoside A (FTA) is a major active constituent of Forsythia suspensa (Thunb.) Vahl. Forsythia suspensa is a flowering plant widely employed as a traditional Chinese herbal medicine to treat various inflammatory diseases such as nephritis, eye2 swelling, scabies, ulcers, and mastitis; however, the molecular mechanisms underlying its therapeutic effects on bovine endometritis are still unclear. The aim of this study was to explore the role of miRNA and the mechanisms underlying the protective activity of FTA on the inflammation of bovine endometrial stromal cells induced by LPS. Based on previous research, we isolated and cultured bESCs in vitro and categorised them into LPS and LPS+FTA groups with three replicates. Upon reaching 80% confluence, the bESCs were treated with 0.5 µg/mL of LPS or 0.5 µg/mL of LPS + 100 µg/mL of FTA. We, then, performed high-throughput sequencing (RNA-Seq) to investigate the effects of FTA on LPS-stimulated primary bESCs and their underlying mechanisms. We identified 167 miRNAs to be differentially expressed in the LPS groups; 72 miRNAs were up-regulated and 95 were down-regulated. Gene ontology enrichment analysis revealed that differentially expressed microRNA (DEGs) were most enriched during the cellular metabolic process; they were mostly located intracellularly and participated in protein, enzyme, and ion binding. Kyoto Encyclopedia of Genes and Genomes pathway analysis revealed that the DEGs were most enriched in the mitogen-activated protein kinase, tumour necrosis factor, and Interleukin-17 signalling pathways. These results reveal the complex molecular mechanism involved in the FTA and provide a basis for future studies of the treatment of bovine endometritis with traditional Chinese medicine monomer.